Exact traveling wave solutions for power law and Kerr law non linearity using the exp(-phi ( xi ))-expansion method (Global Journal of Science Frontier Research, 2014)
The exp(-‘ (»))-expansion method is used as the first time to investigate the wave solution of the nonlinear Burger equation with power law nonlinearity, the perturbed non-linear Schrodinger equation with kerr law nonlinearity. The proposed method also can be used for many other nonlinear evolution equations.
Keywords: exp('(»))-expansion method; homogeneous balance; travelling wave solutions; solitary wave solutions; the nonlinear burger equation with power law